The Problems of Learning Islamic Religious Education in the New Normal Period in North Sumatra - Munawir Pasaribu (Budapest International Research and Critics University, 2022)
The Covid pandemic period, which does not know when it will end, has caused many problems for our nation, the problems caused not only have an impact on the government system but all lines. The economy plummeted, tourism declined, and the most impact was on the current education system. Education seems to be in suspended animation, helpless in what to do, the government is afraid to open schools for students, it is feared that it will add a new cluster in the spread of this covid. The closing of schools and being replaced with online learning creates many new problems for parents, teachers and the community. Many students do not get detailed and maximal learning, not to mention the internet network problems they face are sometimes a problem. Especially in learning Islam, many students have problems related to understanding Islamic learning because there are practical learning materials that must be carried out by students. Therefore, in this study, we will discuss the problems of learning Islamic Religious Education in the New Normal Period in North Sumatra. This research is a qualitative research with a case study approach, with respondents from schools in North Sumatra. Data collection techniques were carried out by observation, interviews and documentation, while the validity of the data was used by using descriptive data analysis techniques to be obtained through a qualitative approach where the data could be generated through research and studies both theoretically and empirically. In addition, to ensure the validity of the data, data triangulation is used. From the results of the study, it was found that Islamic religious education learning in the new normal period was very ineffective for students and it was feared that the Islamic values (uswah hasanah) that students would get from the teacher were not found in their entirety when learning online.